Judge Bork Is Wrong: The Covenant Is the Law - John Quigley (Washington University Law Quarterly, 1993)
This Article examines the U.S. ratification of the International Covenant on Civil and Political Rights in light of Judge Bork's position and the Senate declaration. The Article also focuses on determining the proper status of the Covenant before U.S. courts.
Keywords: Human rights; Robert Bork; 1927-; International Covenant on Civil & amp; Political Rights (1966)